2020
DOI: 10.1016/j.sjbs.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Repeat oral dose safety study of standardized methanolic extract of Boswellia sacra oleo gum resin in rats

Abstract: The oleo gum resin of Boswellia sacra Fleuck. (Burseraceae) is widely consumed for treatment of several diseases and disorders. To determine the effect of repeated administration of this resin on liver and kidney functions, three different doses of standardized methanolic extract were administered orally to rats for 28 days. Apart from histological studies and determination of biomarkers of hepatotoxicity and nephrotoxicity, other parameters of sub-chronic toxicity such as behavioral change, food consumption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…In mice, no death was recorded following the single-dose administration of B. serrata extract at a dose of up to 5 g/kg (Gomaa et al 2019 ). Oral administration of the extract for 28 consecutive days did not exhibit any sign of behavioral toxicity and did not show significant changes of biomarkers of hepatic and renal functions as well as the histological characters in rats (Al-Yahya et al 2020 ). Moreover, Alluri et al ( 2019 ) demonstrated that repeated oral dose of B. serrata extract for 28 days in Wistar rats did not show dose-related signs of toxicity on the hematology, clinical chemistry, mutagenic, and clastogenic parameters.…”
Section: Toxicity and Safety Of B Serrata Extract And Boswellic Acidsmentioning
confidence: 99%
“…In mice, no death was recorded following the single-dose administration of B. serrata extract at a dose of up to 5 g/kg (Gomaa et al 2019 ). Oral administration of the extract for 28 consecutive days did not exhibit any sign of behavioral toxicity and did not show significant changes of biomarkers of hepatic and renal functions as well as the histological characters in rats (Al-Yahya et al 2020 ). Moreover, Alluri et al ( 2019 ) demonstrated that repeated oral dose of B. serrata extract for 28 days in Wistar rats did not show dose-related signs of toxicity on the hematology, clinical chemistry, mutagenic, and clastogenic parameters.…”
Section: Toxicity and Safety Of B Serrata Extract And Boswellic Acidsmentioning
confidence: 99%
“…The anti-aggregatory effect of boswellic acid in high-fat fed rats found a variation in the boswellic acid in a dose-dependant manner. Al-Yahya et al [ 24 ] reported that the boswellic acid is safe up to 1000 mg/kg in rats. Still, this dose is relatively high considering the amount of extract consumed by humans.…”
Section: Discussionmentioning
confidence: 99%
“…The utilized doses of boswellic acid in the current study were tested previously as showed by Sami et al [ 21 ] and Nusier et al [ 20 ] as well as Barakat et al [ 22 ] and Tawfik et al [ 23 ]. Al-Yahya et al [ 24 ] reported that the boswellic acid is safe up to 1000 mg/kg in rats. Still, this dose is relatively high, considering the amount of extract consumed by humans.…”
Section: Methodsmentioning
confidence: 99%
“…is gum resin's water extract, known as "Moh-Lubban," is traditionally used to treat coughs and stomach problems [1].…”
Section: Traditional Medicinementioning
confidence: 99%
“…Boswellia sacra Flueck is a perennial plant belonging to the family Burseraceae. Aromatic oleo-gum-resin extracted from B. sacra, known as frankincense or olibanum (Figure 1), is used as a home remedy, especially in Middle East countries [1]. Frankincense is harvested by making shallow incisions into the tree trunk [2].…”
Section: Introductionmentioning
confidence: 99%